(untitled) (Linguist, 2025)
I don’t mean from this article a technical examination of the Covid epidemic; I mean only to his rhetorical effects of the disorder of the speech about him because of his mystery. That’s why everyone got involved; Scientists and scientists, in debate and in equal measure. It is in this context that scientists and politicians have drawn the metaphor to describe this deadly epidemic. The war metaphor was the most famous one ever circulated. This article has the benefits and disadvantages of using this metaphor. One metaphor for describing a phenomenon is always inadequate. While the multiplicity of metaphors to describe the phenomenon may bring us closer to it without being able to take full notice of it.